Genome-wide association and transcriptome analysis suggests total serum ghrelin to be linked with GFRAL. Issue 6 (10th May 2021) - Wittekind, Dirk Alexander; Scholz, Markus; Kratzsch, Jürgen; Löffler, Markus; Horn, Katrin; Kirsten, Holger; Witte, Veronica; Villringer, Arno; Kluge, Michael
Abstract : Objective: Ghrelin is an orexigenic peptide hormone involved in the regulation of energy homeostasis, food intake and glucose metabolism. Serum levels increase anticipating a meal and fall afterwards. Underlying genetic mechanisms of the ghrelin secretion are unknown. Methods: Total serum ghrelin was measured in 1501 subjects selected from the population-based LIFE-ADULT-sample after an overnight fast. A genome-wide association study (GWAS) was performed. Gene-based expression association analyses (transcriptome-wide association study (TWAS)) are statistical tests associating genetically predicted expression to a certain trait and were done using MetaXcan. Results: In the GWAS, three loci reached genome-wide significance: the WW-domain containing the oxidoreductase-gene (WWOX; P = 1.80E-10) on chromosome 16q23.3-24.1 (SNP: rs76823993); the contactin-associated protein-like 2 gene (CNTNAP2; P = 9.0E-9) on chromosome 7q35-q36 (SNP: rs192092592) and the ghrelin And obestatin prepropeptide gene (GHRL; P = 2.72E-8) on chromosome 3p25.3 (SNP: rs143729751). In the TWAS, the three genes where the expression was strongest associated with serum ghrelin levels was the ribosomal protein L36 (RPL36; P = 1.3E-06, FDR = 0.011, positively correlated), AP1B1 ( P = 1.1E-5, FDR = 0.048, negatively correlated) and the GDNF family receptor alpha like (GFRAL), receptor of the anorexigenic growth differentiation factor-15 (GDF15), ( P = 1.8E-05, FDR = 0.15, also negatively correlated). Conclusions: The three genome-wide significant genetic loci from the GWA and the genes identified in the TWA are functionally plausible and should initiate further research.